Human Rights in the Control of Digital Public Space Freedom: A Collaborative Approach Based on Islamic Law Principles - Shaleh, Chaerul; Rasyid, Fauzan Ali; Sonjaya, Adang; Abdulrahman, Manswab Mahsen (Jurnal Hukum Islam, 2025)
Internet control has a close relationship with human rights because the digital space is becoming increasingly integral to social, political, and economic life. The purpose of this study is to discuss Internet control policies that support or hinder human rights and identify the right approach to solving problems related to existing problems. The research method adopts a normative juridical approach with a statute and conceptual approach. This study found that internet and social media regulations, namely Electronic Information and Transactions Law, have rubber articles that can be misused to limit freedom of expression, thus having implications for socio-political conditions, namely reducing people’s space to express their opinions, threatening democracy and political participation, including the implementation of Islamic Law in local governments based on Sharia. The researcher argues that a collaborative approach based on Islamic law, which includes truth and honesty (Sidiq), justice and equality (Adil), politeness and respect (Hilm), and preventing damage and conflict (Munkar), can be the most appropriate solution to solve existing problems in Indonesia. This study contributes to the formation and implementation of policies to address potential conflicts between freedom of expression and national security in Indonesia and various countries that have the same problems.